Mediterranean Species of the Spittlebug Genus Philaenus: Modes of Chromosome Evolution - Maryańska-Nadachowska, Anna (University of Wisconsin Library, 2012)
The evolution of karyotypes and sex determination system of Philaenus Stål (Auchenorrhyncha: Aphrophoridae) species is studied here in detail. The most plausible scenario of chromosomal rearrangements accompanying phylogenetic differentiation in Philaenus is advanced. It is postulated that the ancestral karyotype of Philaenus was 2n = 24 + X0. Karyotype changes occurred several times independently in the genus. The karyotype of 2n = 22 + X0 (P. spumarius and P. tesselatus) originated from 2n = 24 + X0 by fusion between two autosomal pairs. The neo—XY system (P. arslani, P. loukasi, P. signatus, P. maghresignus, and P. tarifa) also originated from the 24 + X0 karyotype by means of independent fusions between autosomes and the original X chromosome. The neo—X(1)X(2)Y system (P. italosignus) evolved from the 2n = 22 + neo—XY karyotype by an additional fusion between the Y chromosome and one more autosomal pair. The neo—X(n)Y system of P. italosignus is the first reported case of an evolutionarily fixed multiple sex chromosome system in Auchenorrhyncha.